1999
DOI: 10.1097/00004728-199909000-00031
|View full text |Cite
|
Sign up to set email alerts
|

Comparison and Evaluation of Rigid, Affine, and Nonrigid Registration of Breast MR Images

Abstract: Nonrigid registration significantly reduces the effects of movement artifact in subtracted contrast-enhanced breast MRI. This may enable better visualization of small tumors and those within a glandular breast.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
60
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(60 citation statements)
references
References 14 publications
0
60
0
Order By: Relevance
“…In practise, however, motion artifacts in the subtracted images can prevent a reliable diagnosis. Our non-rigid registration algorithm [3] has been shown to significantly reduce the effects of movement artifacts in subtracted contrast-enhanced breast MR images [4] and thus should support the detection of enhanced lesions. Non-rigid transformations can generally change not only the shape but also the volume of image features [5], yet the short MR acquisition time makes volume changes during a scan sequence physically implausible.…”
Section: Introductionmentioning
confidence: 99%
“…In practise, however, motion artifacts in the subtracted images can prevent a reliable diagnosis. Our non-rigid registration algorithm [3] has been shown to significantly reduce the effects of movement artifacts in subtracted contrast-enhanced breast MR images [4] and thus should support the detection of enhanced lesions. Non-rigid transformations can generally change not only the shape but also the volume of image features [5], yet the short MR acquisition time makes volume changes during a scan sequence physically implausible.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting images are standard MRA images without image registration. Additionally automated image registration with linear, affine and warp registration was applied to optimally fit the unenhanced image volume to its contrastenhanced counterpart [14,15]. This was done with the freeware automated image registration software package AIR 5.2.5 (Woods RP, AIR 5.2.5, http://bishopw.loni.ucla.…”
Section: Postprocessing With Automated Image Registrationmentioning
confidence: 99%
“…Previously, an algorithm has been devised for the non-rigid registration of images [4] and applied to CE MR-mammograms. It was shown that this registration method significantly improved the quality of the pre-and post-contrast image difference [5].…”
Section: Introductionmentioning
confidence: 96%